Representation of solutions of linear differential systems of second-order with constant delays - Svoboda, Z. (Нелінійні коливання, 2016)
We derive representations for solutions to initial-value problems for n-dimensional second-order differential equations with delays, x''(t) = 2Ax' (t − τ ) − (A² + B² )x(t − 2τ), and x''(t) = (A + B)x' (t − τ ) − ABx(t − 2τ ), by means of special matrix delayed functions. Here A and B are commuting (n × n)-matrices and τ > 0. Moreover, a formula connecting delayed matrix exponential with delayed matrix sine and delayed matrix cosine is derived. We also discuss common features of the two considered equations. Знайдено зображення розв’язкiв задач iз початковими умовами для диференцiальних рiвнянь другого порядку розмiрностi n iз запiзненнями x''(t) = 2Ax' (t − τ ) − (A² + B² )x(t − 2τ), та x''(t) = (A + B)x' (t − τ ) − ABx(t − 2τ ), при цьому використано спецiальнi матричнi функцiї iз запiзненням. Тут A i B — комутативнi матрицi розмiрностi n × n i τ > 0. Також отримано формулу, що зв’язує експоненцiальну матрицю з запiзненням з sin- та cos-матрицями iз запiзненням. Також розглянуто загальнi властивостi обох розглядуваних рiвнянь.